Single use versus reusable digital flexible ureteroscopes: A prospective comparative study. (25th August 2019) - Kam, Jonathan; Yuminaga, Yuigi; Beattie, Kieran; Ling, Koi Yi; Arianayagam, Mohan; Canagasingham, Bertram; Ferguson, Richard; Varol, Celalettin; Khadra, Mohamed; Winter, Matthew; Ko, Raymond
Abstract : Objectives: To compare the performance and surgical outcomes of two different single‐use digital flexible ureteroscopes with a reusable video flexible ureteroscope. Methods: Patients undergoing retrograde flexible ureteroscopy at Nepean Hospital, Sydney, Australia, were included in this study. Three different flexible ureteroscopes were used in this study: (i) single‐use digital LithoVue (Boston Scientific, Marlborough, MA, USA); (ii) single‐use digital PU3022A (Pusen, Zhuhai, China); and (iii) reusable digital URF‐V2 (Olympus, Tokyo, Japan). Visibility and maneuverability was rated on a 5‐point Likert scale by the operating surgeon. Operative outcomes and complications were collected and analyzed. Results: A total of 150 patients were included in the present study. Of these, 141 patients had ureteroscopy for stone treatment, four for endoscopic combined intrarenal surgery and five for diagnostic/tumor treatment. There were 55 patients in the LithoVue group, 31 in the PU3022A group and 64 patients in the Olympus URF‐V2 group. The URF‐V2 group had higher visibility scores than both the single‐use scopes and higher maneuverability scores when compared with the PU3022A. The LithoVue had higher visibility and maneuverability scores when compared with the PU3022A. There were no differences in operative time, rates of relook flexible ureteroscopes, scope failure or complication rates observed. Conclusions: Single‐use digital flexible ureteroscopes have visibility and maneuverability profiles approaching that of a reusable digital flexible ureteroscope. Single‐use flexible ureteroscopes achieve similar clinical outcomes to the more expensive reusable versions.